2018
DOI: 10.3390/en11040916
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fracture Heterogeneity Using Linear Congruential Generator (LCG) on the Thermal Front Propagation in a Single Geothermal Fracture-Rock Matrix System

Abstract: An implicit finite difference numerical model has been developed to investigate the influence of fracture heterogeneity on the propagation of thermal front in a single horizontal fracture-matrix system. Instead of depending on a complex and data-demanding geostatistical method for a precise representation of fracture aperture, a statistical linear congruential generator (LCG) method was applied in the present study to replicate the unpredictable nature of fracture aperture morphology. The results have been com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This Darcy flux is proportional to the hydraulic gradient as given in eqn. (2). The parameter C represents the coefficient of proportionality as given in eqn.…”
Section: Darcy's Law and Its Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Darcy flux is proportional to the hydraulic gradient as given in eqn. (2). The parameter C represents the coefficient of proportionality as given in eqn.…”
Section: Darcy's Law and Its Extensionmentioning
confidence: 99%
“…, geothermal reservoirs (Suresh Kumar and Ghassemi, 2005; Suresh Kumar and Ghassemi, 2006;Ghassemi and Suresh Kumar, 2007;Rakesh and Suresh Kumar, 2016;Bagalkot et al, 2018), shale gas reservoirs (Patwardhan et al, 2014;Samarth et al, 2015;Samarth et al, 2016), coal bed methane reservoirs and deep saline aquifers (Vivek and Suresh Kumar, 2016;Vivek et al, 2017). Since, flow through a classical homogeneous porous medium in itself has huge complexities, there are still a number of unresolved fundamental queries.…”
mentioning
confidence: 99%
“…One such measuring tool can be "Rock Saturation Factor" (RSF) developed in the present study. RSF effectively measures the extent of penetration/diffusion of suspended particles/colloids within the porous rock matrix (developed based on Bagalkot et al [21]). RSF gives the information on the extent of the diffusion for various size and density of colloids or any suspended particle or solute within the rock matrix from the fracture.…”
Section: Rock Penetration Length and Rock Saturation Factormentioning
confidence: 99%
“…Pandey et al found that thermochemical and thermomechanical effects were the most important consequences of heterogeneity [23]. Nikhil et al simplified the crack model by a statistical linear congruent generator method, and carried out sensitivity analysis of fracture aperture size and fluid flow [24].…”
Section: Introductionmentioning
confidence: 99%